A new gas chromatographic method for quantification of Metformin hydrochloride and Vildagliptin in bulk and pharmaceutical dosage form: development and validation - Popat Mohite; Ramesh Bhusal; Yogita Khandre; Ramdas Pandhare; Anil Pawar (SpringerOpen, 2024)
Abstract Background Metformin, an antidiabetic drug, assists in reducing the creation of glucose inside the liver. Vildagliptin, a DPP-4 inhibitor, enhances insulin release from the pancreas and reduces the hormones that elevate blood sugar levels. The combined medications work synergistically to lower blood sugar levels. This study was designed to develop and validate a reliable method of simultaneous assessment of Metformin and Vildagliptin in bulk and pharmaceutical dosage forms. For the chromatographic separation, a Gs-Tek INNOWAX column was utilized. This column has a length of 30 m, an internal diameter of 0.25 mm, and a 1.8 µm film thickness. For the detection, a Flame Ionization Detector was utilized. The ideal conditions included an injection volume of 1 µL with a split mode of 10 to 1 ratio, a flow rate of 1 mL/minute for the nitrogen carrier gas, an injector temperature of 300 °C, a detector temperature of 250 °C, an initial oven temperature of 100 °C that was maintained for seven minutes and then programmed to climb at a rate of 10 °C per minute up to a temperature of 300 °C. Results A gas chromatographic method that is simple, precise, accurate, robust, and reliable has been developed and implemented for the simultaneous estimation of Metformin and Vildagliptin in the tablet dosage form. The retention time for Metformin and Vildagliptin was 10.203 and 22.021 min. respectively. Validation studies were performed on the method's Linearity, detection limit (LOD), and quantitation limit (LOQ), as well as its accuracy, precision, system suitability, and robustness, using the norms established by the International Conference on Harmonization (ICH). The mean recovery value for Metformin and Vildagliptin was 100.31% (% R.S.D. = 0.6743%) and 100.33% (% R.S.D. = 0.6900%). All the results are within the acceptable range. Conclusion Validation of the developed method revealed that all the results were within an acceptable range, and techniques can be employed to analyze these two medications in combined dosage forms. It is the first method used for simultaneous estimation of these two drugs. Graphical abstract